The Effect of Private Visiting and Promotion Strategy on Tourist Interest Visiting in Bali City - Wayan Ardani; Ashfaq Hossain Khan; Iis Noviyanti; Mohammad Farhan Zeb Khan (Har Press Indonesia, 2020)
This study aims to determine the effect of tour guides and promotional strategies on the interest of tourists visiting Bali. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that the guide has a significant effect on tourist interest by 43.2%, hypothesis testing is obtained t count> t table or (8,452> 1.986). Promotion strategy has a significant effect on tourist interest by 43.9%, hypothesis testing is obtained t count> t table or (8,576> 1,986). Tour guides and promotion strategies simultaneously have a significant effect on tourist interest with the regression equation Y = 9.311 + 0.372X1 + 0.406X2. The contribution of the effect was 53.7%, the hypothesis test obtained F count> F table or (53.950> 2,700).